Genetically modified organisms - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
R Tripp. 1999. ISSN 0140 8682 Free of charge.Overseas Development Institute (ODI),Portland House, Stag Place, London SW1E 5DP, UK.Fax: +44 171 393 1699Email: publications@odi.org.ukAlso available on the Internet at: www.oneworld.org/odi/